2021
DOI: 10.1093/jcag/gwab033
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s and Colitis Canada’s 2021 Impact of COVID-19 and Inflammatory Bowel Disease in Canada: COVID-19 Vaccines—Biology, Current Evidence and Recommendations

Abstract: The COVID-19 pandemic has ushered a globally focused vaccine development program that produced multiple successful vaccines within a year. Four SARS-CoV-2 vaccines have been approved for use in Canada, using two different technologies, all of which have shown excellent efficacy in reducing the rate of symptomatic COVID-19 infection and 100% efficacy in preventing death from COVID-19. People with inflammatory bowel disease (IBD), like many others with immune-mediated chronic diseases, were excluded from the piv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…A three-dose SARS-CoV-2 vaccination schedule for individuals with IBD has been proposed based on impaired serological responses to two-dose regimens. 12,21,22 Our study demonstrates near complete seroconversion to 3 rd dose vaccination with significantly higher antibody titres when compared to 2 nd dose vaccination. Third dose antibody responses are consistently high across all IBD therapies for maintenance of remission including biologic and immunomodulator therapies.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…A three-dose SARS-CoV-2 vaccination schedule for individuals with IBD has been proposed based on impaired serological responses to two-dose regimens. 12,21,22 Our study demonstrates near complete seroconversion to 3 rd dose vaccination with significantly higher antibody titres when compared to 2 nd dose vaccination. Third dose antibody responses are consistently high across all IBD therapies for maintenance of remission including biologic and immunomodulator therapies.…”
Section: Discussionmentioning
confidence: 56%
“…7 Consequently, gastroenterology organizations and public health officials have recommended three-dose vaccine regimens for individuals with IBD. 12 Despite recommendations, uptake of 3 rd dose vaccines remains low in the IBD population. 13…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the included studies are illustrated in Table 1 [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . The details of the excluded studies with the reason for exclusion is shown in Supplementary Table 2 [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] .
Figure 1 PRISMA flow chart depicting the study screening and selection of the systematic review
…”
Section: Resultsmentioning
confidence: 99%
“…However, people who are immunocompromised were excluded from the initial randomised trials despite concerns that they were at increased risk of severe COVID‐19. This paradox and consequent lack of evidence resulted in recommendations for COVID‐19 vaccines for inflammatory bowel disease (IBD) patients that were extrapolated from other populations 1,3 . The scientific community moved quickly to address vaccine safety and effectiveness with prospective observational research and routinely collected health data.…”
mentioning
confidence: 99%